Análise de risco no descomissionamento de dutos rígidos submarinos - Ramos, Rafaela de Andrade (2018)
The decommissioning stage of underwater structures has gained momentum in recent years, as the number of facilities at the end of their useful lives is increasing and legislation becomes more severe. Unlike the production units, which already have their decommissioning plans consolidated, submarine pipelines today represent the greatest technological, environmental and financial challenge of this stage. In this way, the present work seeks to elaborate a risk analysis for the main options of decommissioning of submarine pipelines, in order to contribute to the decision making and reduction of failures. For this, two Fault Trees will be built, the first for the reverse reeling decommissioning and the second for the abandon option, followed by the subsequent elaboration of its minimum cuts. Once the first order minimum cuts are identified, the risk classification matrices for these events will be elaborated. The main results show that the main unacceptable risks are associated with the events of human failure, failure in the dynamic positioning system of the vessel, failure in the tensioner and failure in the motor of the reeling, and these risks must be reduced by restructuring the projects and /or the creation of security barriers.